Casting and inkjet printable photochromic films based on polymethylmethacrylate – Phosphotungstic acid - Espindola, A.; Gonçalves, N. S.; Nalin, M. [UNESP]; Ribeiro, S. J.L. [UNESP]; Barud, H. S.; Molina, C. (Elsevier, 2019)
The incorporation of polyoxometalates in suitable matrices has been a main effort to produce transparent photochromic materials. Polymeric films based on high transparent polymethylmethacrylate (PMMA) containing phosphotungstic acid (PWA) have been obtained by casting and also by inkjet printing. In this investigation, polymeric PMMA matrix containing PWA were developed in an appropriate ratio of CH2Cl2/THF solvents to provide suitable transparent solution. PMMA/PWA composites obtained by casting were characterized by IR-ATR, Raman, XRD, TG/DTG, UV–Vis. Inkjet printing solution were characterized by surface tension (ST), viscosity and contact angle (CA) on glass substrate and films by optical microscopy. Infrared-ATR and Raman spectroscopies showed that the polyoxometalate structure was preserved in the polymeric matrix and the interaction between them occurred due to electrostatic forces. XRD indicated that PMMA and photochromic films were amorphous and display thermal stability up to 300 °C. Upon the UV irradiation, transparent films become blue and the photobleaching process were performed as a function of the temperature in a presence of air. These high transparent and photosensitive photochromic films present potential application as coating by casting and miniatured devices by inkjet printing.
Keywords: Casting; Inkjet printing; Phosphotungstic acid; Photochromic; Polymethylmethacrylate